Evaluation of Phytase Producing Bacteria for Their Plant Growth Promoting Activities - Prashant Singh; Vinod Kumar; Sanjeev Agrawal (International Journal of Microbiology)
Bacterial inoculants are known to possess plant growth promoting abilities and have potential as liquid biofertilizer application. Four phytase producing bacterial isolates (phytase activity in the range of 0.076–0.174 U/mL), identified as Advenella species (PB-05, PB-06, and PB-10) and Cellulosimicrobium sp. PB-09, were analyzed for their plant growth promoting activities like siderophore production, IAA production, HCN production, ammonia production, phosphate solubilization, and antifungal activity. All isolates were positive for the above characteristics except for HCN production. The solubilization index for phosphorus on Pikovskaya agar plates was in the range of 2–4. Significant amount of IAA (7.19 to 35.03 μg/mL) production and solubilized phosphate (189.53 to 746.84 μg/mL) was noticed by these isolates at different time intervals. Besides that, a greenhouse study was also conducted with Indian mustard to evaluate the potential of these isolates to promote plant growth. Effect of seed bacterization on various plant growth parameters and P uptake by plant were used as indicators. The plant growth promoting ability of bacterial isolates in pot experiments was correlated to IAA production, phosphate solubilization, and other in vitro tests. On the basis of present findings, isolate PB-06 was most promising in plant growth promotion with multiple growth promoting characteristics.